Current Understanding of Atrophic Gastritis and Intestinal Metaplasia as a Premalignant Lesion of Gastric Cancer - Zornitsa Gorcheva (Journal of Biomedical & Clinical Research)
Gastric cancer is the fifth most common and third leading cause of cancer death worldwide. Patients with chronic atrophic gastritis (CAG) and intestinal metaplasia (IM) are at increased risk of developing gastric cancer (GC). It is common for CAG to precede IM, but the etiology of the two conditions is not always the same. Different scoring systems are used to assess HAG, MI, and GC risk, making it difficult to interpret results from investigations and management of these conditions.